2017
DOI: 10.1177/1756283x17731520
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the management of Wilson’s disease

Abstract: Abstract:Wilson's disease is a rare, inherited autosomal recessive disease of copper metabolism, in which the causative gene, ATP7B, results in absent or reduced function of the ATP7B transporter important for biliary excretion of copper and incorporation of copper into caeruloplasmin. Affected patients accumulate excessive copper within the liver, brain and other tissues. A disease mainly of children, adolescents and young adults; clinical features vary from the asymptomatic state to chronic liver disease, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 99 publications
(199 reference statements)
1
39
0
1
Order By: Relevance
“…In addition, blood copper concentration decreased and urine copper concentration increased after administration of penicillamine. These findings were consistent with those observed in human patients with WD . Thus, these findings suggest that penicillamine can be effective in the treatment of cats with PCH, and blood and urine copper concentrations can be used as the markers of the response to treatment.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, blood copper concentration decreased and urine copper concentration increased after administration of penicillamine. These findings were consistent with those observed in human patients with WD . Thus, these findings suggest that penicillamine can be effective in the treatment of cats with PCH, and blood and urine copper concentrations can be used as the markers of the response to treatment.…”
Section: Discussionsupporting
confidence: 89%
“…Up to 30% of WD patients have manifested with psychiatric symptoms at the time of diagnosis . WD is mainly diagnosed between ages 5 and 35 years, but it can occur at any age . WD is a common disease, but it is infrequently recognized …”
mentioning
confidence: 99%
“…PCA is a non-specific metal chelating agent that is commonly used to treat WD by gradually increasing the prescribed dose from a relatively low baseline dose to a therapeutically effective dose (Joyce, 1990). While the modality of PCA treatment may aggravate neurological symptoms, continued treatment or changes in the prescribed dose may improve the condition (Kathawala and Hirschfield, 2017). For example, Walshe (Walshe and Yealland, 1993) found that PCA was effective in 97 out of 137 patients with WD who presented with neurological symptoms; however, 24 patients had a poor response to PCA treatment, and 20 patients died.…”
Section: Discussionmentioning
confidence: 99%